Interaction and Contribution of Money Supply, Unemployment, Economic Growth, Sharia and Conventional Monetary Instruments to Inflation - Hasibuan, Indra Mualim; Batubara, Maryam; Bi Rahmani, Nur Ahmadi (MediaTrend, 2024)
Controlling inflation to create economic stability is an absolute must for the government. However, there are challenges to creating stable inflation, including the existence of variables in the money supply, unemployment and economic growth which have an impact on creating inflation. In an effort to overcome these challenges, the government uses sharia and conventional monetary instruments to control inflation. In 2022, the improvement in the Indonesian economy after the Covid 19 pandemic will actually create the highest inflation in recent years. The aim of this research is to determine the interaction and contribution of Money Supply, Unemployment, Economic Growth, Government Sharia Securities, Islamic Interbank Money Market, Bank Indonesia Certificate, and Interbank Money Market to Inflation using monthly data from 2015-2022. This research is quantitative research using the VECM method with the help of E-Views software. Research results: Money Supply has a negative and insignificant effect on Inflation, Unemployment and Economic Growth have a positive and insignificant effect on Inflation, SBSN has a negative and insignificant effect on inflation, PUAS has a negative and significant effect on Inflation, SBI and PUAB have a positive and insignificant effect against inflation. The implication of the research is that the monetary authority, in this case Bank Indonesia, as the institution authorized to control inflation, is to prioritize the SBSN and PUAS monetary instruments to control inflation. Research limitations include only using a few monetary instruments, due to limited data available on various government websites for several years. Keywords: Inflation, Money Supply, Unemployment, Economic Growth, SBSN, PUAS, SBI, PUAB